Pengaruh Kesesuaian Kompensasi Dan Pengendalian Internal Terhadap Kecenderungan Kecurangan Akuntansi - Fani Maretta Putri; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to examine empirically about: 1) the effect of suitability of compensation on accounting fraud tendencies, 2) the effect of internal control on accounting fraud tendencies, 3) the effect of interaction of suitability of compensation and internal control on accounting fraud trends. This type of research is classified as quasi-experimental. The data in this study were collected by questionnaire on 84 accounting students at Padang State University. Analysis was carried out using two way ANOVA. The results of this study conclude that (1) the suitability of compensation has an effect on the tendency of individuals to commit accounting fraud with a significance value of 0,000 <0,05 (2) internal control influences the tendency of individuals to commit accounting fraud with a significance value of 0,000 <0,05 (3) interactions conformity of compensation and internal control towards accounting fraud tendencies with a significance value of 0.046 <0,05